The impact of glutathione S-transferase genotype and phenotype on the adverse drug reactions to azathioprine in patients with inflammatory bowel diseases - Hui Liu; Liang Ding; Fangbin Zhang; Yu Zhang; Xiang Gao; Pinjin Hu; Huichang Bi; Min Huang (Elsevier, 2015)
Azathioprine (AZA) is a thiopurine prodrug which is widely used in patients with inflammatory bowel disease (IBD). However, the use is limited in one-third of patients because of adverse drug reactions (ADRs) or a lack of clinical response. It has been considered that the polymorphic enzyme thiopurine S-methyltransferase (TPMT) plays an important role in the in vivo process of AZA and the occurrence of its myelotoxicity. Glutathione S-transferase (GST) mutation is another pharmacogenetic polymorphism which is probably involved in AZA metabolism and tolerance. The aim of this study was to investigate the association among GST polymorphism, enzyme activity and AZA-related ADRs in Chinese Han patients with IBD. We found that the patients who became neutropenic had a significantly higher GSTs activity when compared with of the patients who did not develop ADRs (analysis of variance, P < 0.001). There was also a significant underrepresentation of GSTP1*-105V allele among patients developing ADRs (odds ratio [OR] = 0.125, 95% confidence interval [CI] = 0.022-0.709, P = 0.0012). The patients with higher GST activity constituted a pharmacogenetic high risk group for leucopenia during AZA treatment. GST-P1 Ile105/Ile105 genotype appeared to be a promising marker indicating predisposition to AZA-related ADRs.